2016
DOI: 10.1039/c6ra14171d
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure and pore size control of template-free synthesised mesoporous magnesium carbonate

Abstract: The structure of mesoporous magnesium carbonate (MMC) first presented in 2013 is investigated using a bottom-up approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 73 publications
8
51
0
Order By: Relevance
“…The increased pore size of ACP053 after storage for 12 months in open air also suggests that the drop in BET surface area was related to the growth of nanoparticles. The same observation has been noted for other similarly structured materials, such as mesoporous magnesium carbonate and HPACC [33,53]; their stability was increased by loading them with guest molecules such as additives or pharmaceuticals. We have also studied the stability of ACP053 in de-ionized water.…”
Section: Stability Of Acpssupporting
confidence: 74%
“…The increased pore size of ACP053 after storage for 12 months in open air also suggests that the drop in BET surface area was related to the growth of nanoparticles. The same observation has been noted for other similarly structured materials, such as mesoporous magnesium carbonate and HPACC [33,53]; their stability was increased by loading them with guest molecules such as additives or pharmaceuticals. We have also studied the stability of ACP053 in de-ionized water.…”
Section: Stability Of Acpssupporting
confidence: 74%
“…Figure 2. The general morphology of MMC (Figure 2a), MMC-Si ( Figure 2c) and MMC-Al (Figure 2e) resemble that previously shown by Cheung et al [11] .The SEM images of calcined NiO/MgO, NiO/MgO-Si and NiO/MgO-Al catalysts showed that the morphology of the MMC support was retained during Ni impregnation and calcination.…”
Section: X-ray Photoelectron Spectroscopy (Xps)supporting
confidence: 83%
“…In all cases, the MMC based supports as well as the NiO containing catalysts appeared to be irregularly shape particles constructed with an assembly of nanometer-sized particles. As discussed in previous studies, the porosity of MMC arises from the space between these nanometer-sized particles [11] . The presence of NiO could also be clearly observed.…”
Section: Intensitymentioning
confidence: 75%
See 2 more Smart Citations